2019
DOI: 10.1136/neurintsurg-2019-015338
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical experience with Cascade: a novel temporary neck bridging device for embolization of intracranial aneurysms

Abstract: BackgroundTemporary placement of a retrievable neck bridging device, allowing parent vessel flow, is an attractive alternative to balloon remodeling for treatment of ruptured intracranial aneurysms.ObjectiveTo present, in a single-center study, our initial experience with Cascade (Perflow, Israel) in the treatment of ruptured intracranial aneurysms.MethodsDuring a period of 1.5 months, 12 patients with aneurysmal subarachnoid hemorrhage underwent coil embolization in conjunction with Cascade in our center. Ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Our observations are based on the fact that adjunctive coil embolisation via either temporary or permanent stenting is used in up to 60% of 260 cases annually by our neurointerventional team -SS (senior) and AS (junior). [11][12][13] The early observations indicate that the device's technical behaviour shows subjective non-inferiority in comparison with the already reported preliminary outcomes of its ancestors -LVIS Jr or any other similar low-profile endoluminal device. [14][15][16][17][18][19] In our limited study sample, the implant demonstrated solid technical success with a good safety profile.…”
Section: Discussionmentioning
confidence: 92%
“…Our observations are based on the fact that adjunctive coil embolisation via either temporary or permanent stenting is used in up to 60% of 260 cases annually by our neurointerventional team -SS (senior) and AS (junior). [11][12][13] The early observations indicate that the device's technical behaviour shows subjective non-inferiority in comparison with the already reported preliminary outcomes of its ancestors -LVIS Jr or any other similar low-profile endoluminal device. [14][15][16][17][18][19] In our limited study sample, the implant demonstrated solid technical success with a good safety profile.…”
Section: Discussionmentioning
confidence: 92%
“…Cascade features denser net and deflected shape during expansion unlike Comaneci. Sirakov et al 12 report less coil entanglement and better compliance with parent vessel during expansion with Cascade compared with Comaneci. The authors acknowledge several limitations of their study, such as the small sample size and lack of long-term follow-up.…”
Section: Advances In Stent-assisted Coilingmentioning
confidence: 99%
“…Although the placement of permanent stents during coiling is associated with greater durability, it is also associated with higher risk of thromboembolic complications. In addition, permanent stents require platelet inhibition, increasing the risk of haemorrhagic complications 12. The Cascade and Comaneci devices provide support during coiling and do not require patients to undergo antiplatelet therapy as they are not permanently deployed.…”
Section: Introductionmentioning
confidence: 99%
“…To date there are two publications regarding the Cascade device. Sirakov et al 20 recently published their early clinical experience with the device. In total, 12 patients with aneurysmal subarachnoid haemorrhage underwent coil embolisation with adjunctive use of the Cascade.…”
Section: Discussionmentioning
confidence: 99%